Matrix Metalloproteinases on Severe COVID-19 Lung Disease Pathogenesis: Cooperative Actions of MMP-8/MMP-2 Axis on Immune Response through HLA-G Shedding and Oxidative Stress - Pedro V. da Silva-Neto; Valéria B. do Valle; Carlos A. Fuzo; Talita M. Fernandes; Diana M. Toro; Thais F. C. Fraga-Silva; Patrícia A. Basile; Jonatan C. S. de Carvalho; Vinícius E. Pimentel; Malena M. Pérez; Camilla N. S. Oliveira; Lilian C. Rodrigues; et al. (Biomolecules, 2022)
Patients with COVID-19 predominantly have a respiratory tract infection and acute lung failure is the most severe complication. While the molecular basis of SARS-CoV-2 immunopathology is still unknown, it is well established that lung infection is associated with hyper-inflammation and tissue damage. Matrix metalloproteinases (MMPs) contribute to tissue destruction in many pathological situations, and the activity of MMPs in the lung leads to the release of bioactive mediators with inflammatory properties. We sought to characterize a scenario in which MMPs could influence the lung pathogenesis of COVID-19. Although we observed high diversity of MMPs in lung tissue from COVID-19 patients by proteomics, we specified the expression and enzyme activity of MMP-2 in tracheal-aspirate fluid (TAF) samples from intubated COVID-19 and non-COVID-19 patients. Moreover, the expression of MMP-8 was positively correlated with MMP-2 levels and possible shedding of the immunosuppression mediator sHLA-G and sTREM-1. Together, overexpression of the MMP-2/MMP-8 axis, in addition to neutrophil infiltration and products, such as reactive oxygen species (ROS), increased lipid peroxidation that could promote intensive destruction of lung tissue in severe COVID-19. Thus, the inhibition of MMPs can be a novel target and promising treatment strategy in severe COVID-19.